Indonesian Tourists’ Perception regarding Singapore’s Tourism Television Commercial - Mohamad Yusuf; Edward Giordan Santoso (Bina Nusantara University, 2020)
The research aimed to highlight the impact of the television commercial (TVC) on Indonesians’ perceptionsregarding tourism in Singapore and their behavioral intention to visit Singapore. The research had five variables:hospitality and comfort/security, infrastructures and superstructures, cultural and natural attractions, perceivedvalues, and behavioral intention. It utilized a quantitative method. About 267 samples were collected using arandom sampling method. Data analysis was drawn from the mean difference for each variable. The findingsindicate that the TVC has positive impacts on the studied variables. The result implies that understanding tourists’perceptions about Singapore as a travel destination will help the stakeholders to formulate appropriate marketingstrategies and position it as a destination choice. However, further research needs to highlight how each variableinfluences tourists’ behavioral intention to revisit Singapore.